MANAJEMEN KEUANGAN DALAM MENINGKATKAN MUTU PENDIDIKAN (Studi Kasus di Kelompok Bermain Nur Masithah Sampang, Madura) - Esi Hairani (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2022)
The aim of the research is to analyze and describe financial management in improving the quality of education in the Nur Masithah Sampang Playgroup. The research method was carried out qualitatively with a case study approach. Data collection techniques by interviewing school principals, teachers, students and parents; documentation techniques; and observation techniques. Data processing techniques with reduction, data presentation, and drawing conclusions. Data validity technique with source and technique triangulation. The results showed: (1) financial management: (a) acquisition of education funds: educational operational assistance funds from the Ministry of Education and monthly student fees. (b) use of education funds for: school administration, assessment and implementation of learning and play, honorarium, subscriptions to resources, maintenance of facilities and infrastructure, admission of new students, library development, health administration, iqra', photocopying, office stationery, print and study tours. (c) distribution of education funds: from the Ministry of Education to schools and forwarded to treasurers (for funds from the Ministry) and from parents to teachers and forwarded to treasurers (for monthly contribution funds). (2) the impact of financial management: management runs smoothly, educational needs are met, learning goes well